A Newly Developed Indicator of Overeating Saturated Fat Based on Serum Fatty Acids and Amino Acids and Its Association With Incidence of Type 2 Diabetes: Evidence From Two Randomized Controlled Feeding Trials and a Prospective Study - Wei, Wei; Zi, Tianqi; Yang, Ruiming; Xu, Jiaxu; Chen, Yunyan; Jiang, XiTao; Chu, Xia; Yang, Xue; Jiang, Wenbo (Frontiers in Nutrition, 2022)
Objective Hyper-caloric intake of saturated fatty acids (SFAs) is common in modern societies, probably contributing to the epidemic of type 2 diabetes mellitus (T2DM). This study conducted two randomized controlled trials (RCTs) for developing a new indicator that can assess the nutritional status and examined its association with incidence of T2DM. Methods In RCT 1, healthy participants were randomly assigned into three groups, namely, control group (n = 40), overfeeding group 1 (100 g butter per day, n = 37), and overfeeding group 2 (120 g butter per day, n = 37). In RCT 2, healthy subjects were randomly assigned into two groups, namely, control group (n = 52) and high-fat group (300-extra kcal/day from diet that was designed by high-fat diet, n = 58). In the prospective cohort, 4,057 participants aged 20–74 years were enrolled and followed up over 5.3 years. Serum profiles of fatty acids and amino acids were measured. Results In RCT 1, serum fatty acids, including C14:0 and C18:0, increased, whereas C18:2, C20:4, C22:5, and C22:6 decreased; serum amino acids, including tyrosine, alanine, and aminobutyric acid, increased, whereas histidine and glycine decreased (p < 0.05). Among these serum fatty acids and amino acids, changes in C14:0, C20:4, tyrosine, histidine, and glycine were also observed in RCT 2. An indicator was developed based on the five fatty acids and amino acids, namely, C14:0 × tyrosine × 1,000/[C20:4 × (glycine + histidine)], and it significantly identified participants in the intervention group with area under the curve (AUC) (95% CI) being 0.85 (0.77–0.92). The indicator was significantly associated with incidence of T2DM in the prospective cohort with HRs (95% CIs) from bottom quartile to top quartile being 1,1.21 (0.82–1.77), 1.60 (1.12–2.30), 2.04 (1.42–2.94). Conclusion The newly developed indicator in RCTs can be used in assessing the nutritional status of hypercaloric intake of SFA and predicting the development of T2DM.